Failure mechanisms of enhancement mode GaN power HEMTs operated in short circuit. (September 2019) - Abbate, C.; Busatto, G.; Sanseverino, A.; Tedesco, D.; Velardi, F.
Abstract: The paper reports the results of a study based on experimental data and finite element simulations about the failure mechanism of 650 V p-doped GaN power HEMT operated in short circuit condition. The study focuses on the failure observed during the short circuit of these devices when the test voltage is larger than 350 V. In this failure mode, the energy involved is quite low and the time to failure is <1 μs. Simulation results show that in these test conditions a very high-power density is dissipated in a critical region of the device and it is intensified by a significant current focalization which has been proved by experimental observations. It is demonstrated that the temperature in the critical region can reach the maximum allowable temperature for a GaN/AlGaN structure. Highlights: GaNs during short circuit fail because the local temperature reaches a critical value. The most sensitive part of the device turns out to be a side of the gate Field Plate. The failure mechanism is not related to a charge-field interaction phenomenon.